Contraintes technologiques au développement du semis direct au Maroc - El Gharras O.; Idrissi M. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
The adoption of no-till in Morocco depends on technology availability at the farmers' level. The seed drill is the biggest constraint to overcome. Since the beginning of the no-till research programme at INRA Settat, the development of a performant and affordable seed drill was identified as the main objective. The collaborative research and development programme initiated in 2001 between INRA and ATMAR (Les Ateliers Marocains) to develop an industrial prototype and then a commercial product still confronts many problems. Even if design development is undergoing, quality control in manufacturing is not satisfying our requirements. The number of prototypes manufactured every year is not economically sustainable and the cost effectiveness is not yet achieved.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)